INNER AUTOMORPHISMS OF NON-COMMUTATIVE ANALOGUES OF THE ADDITIVE GROUP OF RATIONAL NUMBERS - Grigoryan, A.Ye. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
It is proved that the inner automorphisms group of the group A(m, n) are characteristic subgroup in Aut(A(m, n)) for all m > 1 and odd $n ≥$1003, where the groups A(m, n) are known non-commutative analogues of the additive group of rational numbers.
Keywords: automorphisms group, inner automorphism, characteristic subgroup